Air Pollution Quality Monitor (CO, CO2, PM2.5) at Surabaya State University - Damanik, Maresa Nei Britama (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2024)
Exposure to air pollution inhaled every day greatly impacts health. Air pollution occurs anywhere, including in the environment of Surabaya State University. Air pollution originates from vehicle emission gases, combustion activities, and other sources. Due to limitations in obtaining air quality information within Surabaya State University, this study aims to facilitate monitoring of air pollution quality (CO, CO2, PM2.5) within Surabaya State University to improve health quality. This air pollution monitor can measure the concentration of CO, CO2, and PM2.5 where the MQ-7 sensor detects CO (carbon monoxide) gas concentrations, the MQ-135 sensor detects CO2 (carbon dioxide) gas concentrations, DSM501A sensors detect PM2.5 (particulate) concentrations, and the use of IoT as a medium for delivering air pollution quality information that can be accessed through air pollution monitoring websites anywhere and anytime. The pollution monitoring tool has a fairly good performance in measuring the quality of air pollution (CO, CO2, PM2.5) in the environment of Surabaya State University, with an average MQ-7 sensor reading accuracy of 87%, an average MQ-135 sensor reading accuracy of 96.44% and an average DSM501A sensor reading accuracy of 90.68% and can send air pollution monitoring results to the website in real-time. Keywords: Pollution monitor, MQ-7, MQ-135, DSM501A, website.